The impact of Information Technology on the Organization of Financial Management (a field study on Iraqi telecommunications companies Asiacell and Zain in Iraq) - Lecturer: Dured Musa Mahmoud; Tarkan Hussein Dawood; Mohammed Jadaan Hammad (Research Parks Publishers, 2023)
Financial management organization is crucial to the success and sustainability of telecom companies in Iraq Asiacell and Zain in Iraq. Information Technology is an important tool that greatly affects the organization and management processes of financial businesses. It was distributed among the members of this sample, which represents employees of Asia Cell and Zain Iraq, and a random sample was taken, as the number of individuals surveyed reached 180 samples. This research aims to understand the impact of Information Technology on the Organization of Financial Management in Asia Cell and Zain and to reveal the benefits and challenges associated with this modern technology. After analyzing the data and testing the hypotheses, the study reached several primary results, the most important of which was that there was a statistically significant correlation at a significance level of 0.05 between Information Technology and the financial management organization